CleanCap M6 inhibits decapping of exogenously delivered IVT mRNA - Zachary F. Mandell; Andrew Ujita; Jordana Henderson; Anthony Truong; Coleen Vo; Farinaz Rezvani; Nona Abolhassani; Alexandre Lebedev; Chunping Xu; Inna Koukhareva; Stephanie Ramos; Kate Broderick; et al. (Molecular Therapy: Nucleic Acids)
Co-transcriptional capping allows exogenous mRNAs to yield robust protein expression. Identifying additional mRNA modifications that further boost protein output will be crucial for developing more efficacious mRNA therapies. Using in vitro approaches, we found that the co-transcriptional cap analog m7G3'OMepppm6A2′OMepG, CleanCap M6, resists enzymatic decapping and that this decreased susceptibility to decapping correlated with substantially increased protein expression in vivo compared to mRNAs capped using existing industry standards.